Предмет: Алгебра,
автор: dolgachevaal03
10ab+(-5ab+b)^2 при а=корень 9, b=корень 5
Ответы
Автор ответа:
0
10ab+(-5a+b)^2 при а=корень 9, b=корень 5
10ab+(-5a+b)²=10ab+((-5a)²-10ab²+b²) =10ab+25a²-10ab²+b²
25a²+b²=25*(√9)²+(√5)²= 25*9+5=230
10ab+(-5a+b)²=10ab+((-5a)²-10ab²+b²) =10ab+25a²-10ab²+b²
25a²+b²=25*(√9)²+(√5)²= 25*9+5=230
Автор ответа:
0
))
Похожие вопросы
Предмет: Алгебра,
автор: fireflg
Предмет: Математика,
автор: aselya2919
Предмет: Литература,
автор: erkindamela
Предмет: Геометрия,
автор: МашаБориска